1993
DOI: 10.1111/j.1476-5381.1993.tb13476.x
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide is involved in the regulation of angiogenesis

Abstract: The in vivo model of the chick embryo chorioallantoic membrane (CAM) was used to study the involvement of nitric oxide (NO) in angiogenesis. The nitrovasodilator sodium nitroprusside (NaNP) and the amino acid, L-arginine, inhibited angiogenesis, assessed as both collagenous protein biosynthesis and vascular density. NG -monomethyl-L-arginine (L-NMMA), an NO synthase inhibitor, increased both collagenous protein biosynthesis and vascular density, indicating that this agent promotes angiogenesis. These results s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
50
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(54 citation statements)
references
References 7 publications
4
50
0
Order By: Relevance
“…Lau and Ma 26 reported that NO inhibits migration of cultured endothelial cells. Pipili-Synetos et al 27 reported that NO donors inhibit angiogenesis in the chick chorioallantoic membrane and tube formation. In contrast, Guo et al 28 reported that an NO donor stimulated the proliferation of aortic endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Lau and Ma 26 reported that NO inhibits migration of cultured endothelial cells. Pipili-Synetos et al 27 reported that NO donors inhibit angiogenesis in the chick chorioallantoic membrane and tube formation. In contrast, Guo et al 28 reported that an NO donor stimulated the proliferation of aortic endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…NO has been implicated in angiogenesis on the basis of observations in dierent models of angiogenesis, including the chick chorioallantoic membrane (Pipili-Synetos et al, 1993), the rabbit cornea (Ziche et al, 1993b) and dierent tumour types (Gallo et al, 1998). However, these studies oer con¯icting conclusions as to whether NO promotes or inhibits angiogenesis.…”
Section: Discussionmentioning
confidence: 88%
“…Nitric oxide (NO), a mediator with a complex pro®le of biological activity was ®rst implicated in angiogenesis by Pipili-Synetos et al (1993) who reported that the nitric oxide synthase (NOS) inhibitor, nitro-L-arginine methyl ester (L-NAME) enhanced vessel growth in the chick chorioallantoic membrane (CAM) model (Pipili-Synetos et al, 1993). Additional studies indicated that NO donors reduced tissue angiogenesis and tumour neovascularization (Pipili-Synetos et al, 1995;Sakkoula et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…NO production by tumour cells may influence tumour growth and metastasis (Pipili-Synetos et al, 1993;Jenkins et al, 1995). The functions of NO in tumours potentially facilitate tumour growth.…”
Section: Discussionmentioning
confidence: 99%